2021
DOI: 10.3389/fphar.2021.691773
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Plays Protective Effects on LPS-Induced Microglia by Switching M1/M2 Phenotypes and Regulating NLRP3 Inflammasome Activation

Abstract: Parkinson’s disease is a neurodegenerative disorder in which activated microglia may appear prior to motor symptoms, but the specific therapeutic mechanisms remain unclear. This study investigated the potential effects of Edaravone (EDA) on M1/M2 polarization of microglia in rats with dopaminergic neurons damage induced by lipopolysaccharide (LPS) and its mechanism. Rats were randomly grouped as the following (n = 10): Control, EDA alone (10 mg/kg), LPS-model (LPS 5 μg), LPS + EDA (5 mg/kg) and LPS + EDA (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Considering that MyD88 activation may enhance neuroinflammation caused by ischemic stroke, we hypothesized that TJ-5 might potently inhibit neuroinflammation to protect against CIRI ( Figures 8A, B ). In CIRI mice model, we compared the neuroprotective effects of edaravone, a medicine currently used clinically for the treatment of ischemic stroke ( Li et al, 2021 ), and different concentrations of TJ-5. We found that TJ-5 at 15 mg/kg was more effective, as the infarction volume was reduced by approximately 80%, achieving better neuroprotective effects than edaravone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that MyD88 activation may enhance neuroinflammation caused by ischemic stroke, we hypothesized that TJ-5 might potently inhibit neuroinflammation to protect against CIRI ( Figures 8A, B ). In CIRI mice model, we compared the neuroprotective effects of edaravone, a medicine currently used clinically for the treatment of ischemic stroke ( Li et al, 2021 ), and different concentrations of TJ-5. We found that TJ-5 at 15 mg/kg was more effective, as the infarction volume was reduced by approximately 80%, achieving better neuroprotective effects than edaravone.…”
Section: Discussionmentioning
confidence: 99%
“…BV-2 microglial and SH-SY5Y cells were cultured as previously described ( Zhao et al, 2020 ). A lipopolysaccharide (LPS)-stimulated BV-2 cell model was established to mimic severe neuroinflammation induced by multiple inflammatory mediators after reperfusion ( Li et al, 2021 ). BV-2 cells were pretreated with different concentrations of TJ-5 for 2 h before LPS (1 μg/ml) stimulation (#L2880, Sigma, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The Iba‐1 was used as a marker for positive microglia. The polarization of microglia cells was marked by separate antibodies, nitric oxide synthase (iNOS) for M1 microglia and Arg1 (Arginase‐1) for M2 microglia (Li, Dai, et al, 2021; Zhou et al, 2021). Briefly, all selected brain slices were incubated with different antibodies overnight at 4°C, including Iba‐1 (Abcam, 1:500), iNOS (Proteintech, 1:500), Arg1 (Proteintech, 1:500), NLRP3 (Affinity, 1:200) and NF‐κB p65 (Affinity, 1:200).…”
Section: Methodsmentioning
confidence: 99%
“…Montelukast acts as an antagonist of the CysLT-1 receptor and has been found to increase the number of M2 phenotype microglia during the acute phase of stroke ( 155 ). Edaravone is a free radical scavenger used in the treatment of amyotrophic lateral sclerosis (ALS), which has been found to promote the M2 microglia activation in preclinical studies ( 160 , 167 ). In a retrospective study by Enomoto et al, clinical outcomes of patients who underwent endovascular reperfusion therapy and edavarone therapy within two days of admission were compared with patients who underwent endovascular reperfusion alone.…”
Section: Microglia and Modms Directed Treatments For Ischemic Strokementioning
confidence: 99%